Moral caring competency and moral distress among Ghanaian nurses in adult care settings: A descriptive-correlational study - Antwi, Rachel Serwaah; Galanza, Jefferson (Belitung Nursing Journal, 2024)
Background: Nurses in adult care settings frequently encounter moral distress due to the daily ethical obligations they must fulfill. In contrast to other healthcare professionals, nurses often grapple with a heightened frequency of moral dilemmas, resulting in increased moral distress. Objective: This study aimed to explore the levels and relationship between moral caring competency and moral distress among Ghanaian nurses in adult care settings. Methods: This quantitative study utilized a descriptive-correlational design. A multistage sampling was used to select three public hospitals. Simple random sampling was used to recruit 231 nurses from the three public hospitals. Data were collected from June to July 2023 using validated questionnaires. The study utilized frequency and percentages, mean and standard deviation, and Spearman’s Correlation. Results: The nurses had a low level of moral caring competency (M = 2.18, SD = 0.340). The composite moral distress score was 227.31, indicating a high level of moral distress among the nurses. Furthermore, there was a moderate, negative significant relationship between moral caring competency and moral distress (rs = -.474, N = 231, p <0.001).  Conclusions: Nurses in public hospitals had limited personal cognitive, affective, and psychomotor abilities to address patient moral issues. The nurses also experience significant moral distress when delivering patient care. Furthermore, to decrease the level of moral distress, moral caring competency should be strengthened among nurses. Therefore, it is recommended that nurse administrators provide adequate organizational support and implement continuous moral training to improve nurses’ moral caring competency and mitigate their moral distress. Healthcare policymakers are encouraged to develop or refine policies to navigate moral dilemmas and reduce moral distress among nurses. Future studies employing qualitative designs can explore the influence of culture on moral caring competency within the Ghanaian setting.